Social functioning and subclinical psychosis in adolescence: a longitudinal general adolescent population study. (17th July 2019) - Heins, M.; Achterhof, R.; Collip, D.; Viechtbauer, W.; Kirtley, O. J.; Gunther, N.; van Os, J.; Feron, F.; Myin‐Germeys, I.
Abstract : Objectives: To investigate the longitudinal relationship between subclinical psychotic symptoms and social functioning in a representative general population sample of adolescents. Method: Data were derived from a routine general health screening of 1909 adolescents in a circumscribed region. Baseline measurement was in the second grade of secondary school (T0), and follow‐up occurred approximately 2 years later (T1). Social functioning and subclinical psychotic symptoms of hallucinations and delusions were assessed at both time points. Results: Baseline (T0) social problems preceded follow‐up (T1) subclinical delusions, but not T1 subclinical hallucinations. Similarly, T0 delusions preceded social problems at T1, but T0 hallucinations did not. Conclusion: This longitudinal general population study demonstrated a bidirectional association between social problems and delusions, but found no link between social problems and hallucinations. This may reflect a downward negative spiral where delusional thoughts and social problems reinforce each other.